2020
DOI: 10.1590/0037-8682-0206-2019
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with mortality among patients who had candidemia in a university hospital

Abstract: Introduction: Bloodstream infection due to Candida spp. is a primary cause of morbidity and mortality in tertiary hospitals. Methods: In this retrospective study, we included patients with a positive blood culture for Candida spp. after 48 h of hospitalization. Results: A total of 335 patients who had candidemia were included in this study. Risk factors associated with mortality were hospitalization in internal medicine units and surgical clinics, age >60 years, mechanical ventilation, orotracheal intubation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Numerous parameters have been identified as risk factors for mortality after candidemia in critically ill patients. These include a history of congestive heart failure, the presence of solid tumors with metastases, red blood cell transfusions, and the duration of antifungal treatment [ 24 , 43 45 ]. For survival analysis, we selected covariates that were considered clinically relevant or factors that had been associated with 30-day mortality in a multinational observational study in 23 European ICUs [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous parameters have been identified as risk factors for mortality after candidemia in critically ill patients. These include a history of congestive heart failure, the presence of solid tumors with metastases, red blood cell transfusions, and the duration of antifungal treatment [ 24 , 43 45 ]. For survival analysis, we selected covariates that were considered clinically relevant or factors that had been associated with 30-day mortality in a multinational observational study in 23 European ICUs [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this infection can have varying mortality rates, from 12% to 70% (Bassetti, et al, 2019) (Medeiros, et al, 2019) (Pappas, et al, 2018) (Tsay, et al, 2020), which reflects the severity of cases of this disease. Studies have indicated high mortality rates in Brazil due to candidemia, from 43% to 72.2% (Alves, et al, 2020) (Doi, et al, 2016) (Khouri, et al, 2016). It is important to note that 26% (17/63) of the patients who died in the present study did not receive antifungal treatment, since the death occurred before the infection diagnosis.…”
Section: Amphotericinmentioning
confidence: 65%
“…Since these associations were not confirmed with the multivariate regression analysis, they could be just epiphenomena. In other studies with patients with candidemia, higher age was associated with higher mortality, among other factors [ 80 ]. Importantly, the removal of CVC in patients with W. anomalus fungemia in the current review was associated with reduced mortality.…”
Section: Discussionmentioning
confidence: 94%